HUBUNGAN FAKTOR INTERNAL DAN EKSTERNAL DENGAN PRESTASI BELAJAR MAHASISWA PROGRAM STUDI KEPERAWATAN WAINGAPU - ULY AGUSTINE; OKLAN BT LIUNOKAS; DOMIANUS NAMUWALI (JURNAL INFO KESEHATAN, 2014)
Student learning achievement is one of main factors which contributes success on high educational program. It can be measured by GPA (Grade Point Avarage). High GPA is influenced by internal and external factors. This research aim is to find out correlation of internal and external factors with student learning achievement in Nursing Department in Waingapu. This is a quantitative research with descriptive method and a correlation study technique approach. The population of this research is all students in Nursing Department in Waingapu which are 356 students. The research sample is 188 respondents. The sample was taken by non random technique which is purposive sampling. The data was analyzed using univariate, bivariate and multivariate calculations. This research shows that there is a significant correlation of attitude, interest, economical class of parents, student activity in society and their social interaction with their learning achievement. The result also shows that attitude has the most significant correlation toward student learning achievement in Nursing Department in Waingapu.